Phytotoxicity of secondary metabolites isolated from Flourensia oolepis S.F.Blake. - Palacios, Sara Maria (2013)
The aim of this study was to isolate the active principles of Flourensia oolepis S.F.Blake (Asteraceae), which completely inhibited the germination of Raphanus sativus seeds at 10 mg/ml. Flavanone pinocembrin and sesquiterpene ilicol, were isolated by bioassay-guided fractionation. They were active both against monocot and dicot seeds. Pinocembrin was the most active compound, with an IC50(germination) value of 0.24, 3.40, 3.28, and 3.55 mM against Panicum miliaceum, Avena sativa, Lactuca sativa, and R. sativus, respectively; ilicol, however, exhibited IC50(germination) values of 0.67, 2.73, 5.25, and 9.66 mM for the same species, respectively. Pinocembrin and ilicol inhibited root growth and showed IC50(root growth) values of 0.199, 14.68, 8.05, 7.69 mM, and 1.22, 2.90, 7.35, 8.07 mM, against P. miliaceum, A. sativa, L. sativa, and R. sativus, respectively. Pinocembrin and ilicol reduced Allium cepa cell division without chromosome aberrations.